2014
DOI: 10.1590/1516-4446-2014-1380
|View full text |Cite
|
Sign up to set email alerts
|

Decreased plasma neurotrophin-4/5 levels in bipolar disorder patients in mania

Abstract: Objective: To evaluate two poorly explored neurotrophins (NT), NT-3 and NT-4/5, in bipolar disorder (BD). Methods: Forty patients with type I BD (18 in remission and 22 in mania) and 25 healthy controls matched for age, gender, and educational attainment were enrolled in this study. All subjects were assessed by the Mini-International Neuropsychiatric Interview; the Young Mania Rating Scale and the Hamilton Depression Rating Scale were used to evaluate severity of symptoms in BD patients. Plasma levels of NT-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…105 Another clinical study showed that NT-3 and NT-4 are elevated in the depressive phase of BD, 106 possibly indicating an attempt by the organism to defend itself against cellular stress. In turn, Barbosa et al 107 demonstrated decreased NT-3 and NT-4 levels in the manic phase of BD. Given that neurotrophins are essential for neuronal function and survival, it is assumed that the viability of nerve cells can be affected by a persistent reduction of these molecules in the nervous system.…”
Section: Changes In Neuroplasticity and Neurotrophic Signalingmentioning
confidence: 96%
“…105 Another clinical study showed that NT-3 and NT-4 are elevated in the depressive phase of BD, 106 possibly indicating an attempt by the organism to defend itself against cellular stress. In turn, Barbosa et al 107 demonstrated decreased NT-3 and NT-4 levels in the manic phase of BD. Given that neurotrophins are essential for neuronal function and survival, it is assumed that the viability of nerve cells can be affected by a persistent reduction of these molecules in the nervous system.…”
Section: Changes In Neuroplasticity and Neurotrophic Signalingmentioning
confidence: 96%
“…Loch et al also reported increased plasma levels of both NT-3 and NT-4/5 in acutely depressed BD subjects compared to healthy controls; however, they did not find significant differences in NT-3 and NT-4/5 levels after lithium treatment [90]. Contrary to other reports, Barbosa et al reported decreased NT-4/5 plasma levels in BD patients with mania in comparison with controls without significant differences in NT-3 plasma levels between BD patients and controls [91].…”
Section: Other Neurotrophinsmentioning
confidence: 77%
“…NTs do not control directly mood but, they are fundamental in the activity-dependent modulation of networks and changes in plasticity [ 11 ]. Low NT levels have been associated with several affective disorders including bipolar depression (BD) [ 189 , 190 ], depression [ 12 , 191 ], mania [ 192 ], and obsessive compulsive disorders [ 193 ]. In particular, reductions in serum and plasma BDNF have been found in patients affected by depression [ 194 , 195 , 196 ], and in those who committed suicide [ 197 , 198 ].…”
Section: Adipokinesmentioning
confidence: 99%